Cost of Developmental Delay from Prenatal Exposure to Airborne Polycyclic Aromatic Hydrocarbons - Weiland, Katherine (2011)
Early life exposure to ambient polycyclic aromatic hydrocarbons (PAHs) can result in developmental delay. The negative health effects of PAHs have been well-documented but the cost of developmental delay due to PAH exposure has not been studied. The Columbia Center for Children’s Environmental Health previously has reported the significant effect of prenatal exposure to ambient PAHs on delayed mental development at three years, using the Bayley Scales in a cohort of low-income women and children in New York City (NYC). Here we have used the cohort results to estimate the annual costs of preschool special education services for low-income NYC children with developmental delay due to PAH exposure using the Environmentally Attributable Fraction method. The estimated cost of PAH-exposure-related services is over $13.7 million per year for Medicaid births in NYC. This high cost supports policies to reduce level of PAHs in NYC air.